2009
DOI: 10.1007/s00276-009-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and review of myocardial bridges in adult cadaver hearts and angiographs

Abstract: The presence of MB, MBL and degree of luminal narrowing were not associated with the age and gender. Deepness and thickness were a major determinant of significancy of systolic obstruction by MBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 29 publications
7
10
2
4
Order By: Relevance
“…These findings were in accordance with the results stated in literature [5,12,26,28]. According to the results of previous literature, the second common location of the MB was the diagonal branches of AIA and PIA branch of RCA (13.8%, each) [5].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These findings were in accordance with the results stated in literature [5,12,26,28]. According to the results of previous literature, the second common location of the MB was the diagonal branches of AIA and PIA branch of RCA (13.8%, each) [5].…”
Section: Discussionsupporting
confidence: 82%
“…However, Fazliogullari et al [12] In accordance with the results of previous cadaveric studies in Colombian [5] and Kenyan [28] populations, the result of present study revealed higher incidence of MB in male hearts (72.2%) than those of female hearts (27.8%), with no significant statistical difference. However, a female predominance was reported by Konen et al [18].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations